2019
DOI: 10.1038/s41598-019-56379-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity and Prediction of Potential Cultivation Areas of Cistanche Herbs

Abstract: Owing to hostile growth environments and increasing related production, Cistanche plants have decreased in number. The aim of the present study was to evaluate the quality of and to predict potential suitable regions for two official species and two nonofficial species (C. salsa and C. sinensis) by high-performance liquid chromatography and the MaxEnt model. The results indicated that 2′-acetylacteoside was present only in C. deserticola. The compound can be used as a potential chemical marker to discriminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Scientists had studied Cistanche species since 1980s ( Kobayashi and Komotsu, 1983 ). Hundreds of publications had been issued in recent 20 years ( Li et al, 2016 ; Wang et al, 2019 ). The chemical analysis demonstrated that phenylethanoid glycosides, iridoids, betaine, Krebs cycle intermediates, lignans, alditols, oligosaccharides and polysaccharides are the main compounds in Cistanche plants ( Lun et al, 2005 ; Li et al, 2016 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists had studied Cistanche species since 1980s ( Kobayashi and Komotsu, 1983 ). Hundreds of publications had been issued in recent 20 years ( Li et al, 2016 ; Wang et al, 2019 ). The chemical analysis demonstrated that phenylethanoid glycosides, iridoids, betaine, Krebs cycle intermediates, lignans, alditols, oligosaccharides and polysaccharides are the main compounds in Cistanche plants ( Lun et al, 2005 ; Li et al, 2016 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of publications had been issued in recent 20 years ( Li et al, 2016 ; Wang et al, 2019 ). The chemical analysis demonstrated that phenylethanoid glycosides, iridoids, betaine, Krebs cycle intermediates, lignans, alditols, oligosaccharides and polysaccharides are the main compounds in Cistanche plants ( Lun et al, 2005 ; Li et al, 2016 ; Wang et al, 2019 ). Pharmacological research showed that the extracts from Cistanche plants possess a wide spectrum of activities, such as curing kidney deficiency and senile constipation, advancing the ability to study and memorize, enhancing immunity, anti-aging and antifatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Around 1970s and 1980s, C. deserticola was once on the verge of extinction and involved in the “second grade” nationally protected plants in China as well as CITES: Appendix II (Endangered species scientific commission). To meet the increasing demands of C. deserticola in the foreign and domestic TCM markets, attention has been devoted to search areas being suitable for C. deserticola cultivation, 23–25 and the deserts in Northwestern China are demonstrated as the exact choice. Afterward, continuous efforts have been also made toward tackling with the holoparasitic properties, and now, C. deserticola has been widely cultivated in several plantations in Inner Mongolia, Ningxia, Xinjiang, and Gansu provinces.…”
Section: Botanical Description Distribution and Cultivationmentioning
confidence: 99%
“…Through relevant literature [19][20][21], 54 ecological factor data, including meteorological factors, soil type and topographic data, which affect the distribution of Chinese medicinal materials were selected. Among them, meteorological factors played a key role in in uencing the target plants' distribution, including 19 bioclimatic variables, precipitation variables and temperature variables, with a spatial resolution of 30 s, were downloaded from the WorldClim-Global Climate Database (http://worldclim.org/).…”
Section: Variablesmentioning
confidence: 99%